Evidence for πCHR→dM bonding in transition metal carbene compounds (LnMCHR) and its decisive role in the α-agostic effect. Issue 38 (21st September 2022) - Lin, Xuhui; Tian, Weiqin; Wu, Wei; Mo, Yirong
Abstract : A partial triple bonding model is proposed to describe transition metal carbene compounds (L n MCHR) with α-agostic interaction, where the seemingly weak yet decisive πCHR →dM interaction is the true origin of α-agostic interaction. Abstract : It has been generally recognized that the α-agostic interaction (M⋯H–C) in transition metal carbene compounds L n MCHR (R = H, Me etc. ) can be interpreted with a double metal–carbon bonding model. This bonding model involves the reorganization of the σ component, which can be illustrated in terms of three-center two-electron (3c-2e) M–H–C covalent bond as in transition metal alkyl compounds. Herein, we propose an alternative partial triple metal-carbon bonding model to elucidate the agostic interaction in L n MCHR. Apart from the well-defined σ and π bonds, there exists a seemingly weak but decisive third force, namely the πCHR →dM bonding between an occupied π-like symmetric CHR orbital and a vacant metal d orbital, which is the true origin of the α-agostic effect. This partial triple bonding model is authenticated on both Fischer- and Schrock-type carbenes by an ab initio valence bond (VB) method or the block-localized wavefunction (BLW) method, which has the capability to quantify this notable π bonding and further demonstrate its geometric, energetic and spectral impacts on agostic transition metal carbene compounds. We also show that ancillary ligands can modulate the πCHR →dM bonding through electronic and steric effects.